DIGGING UP JERICHO past, present and future. (Archaeopress archaeology., 2019)
21 papers present a holistic perspective on the research and public value of the site of Jericho - an iconic site with a long and impressive history stretching from the Epipalaeolithic to the present day. Covering all aspects of archaeological work from past to present and beyond, they re-evaluate and assess the legacy of this important site.